Optimal Hemodialysis Prescription: Do Children Need More Than a Urea Dialysis Dose?. (24th April 2011) - Michel, Fischbach; Ariane, Zaloszyc; Betti, Schaefer; Claus Peter, Schmitt
Abstract : When prescribing hemodialysis in children, the clinician should first establish an adequate regimen, before seeking to optimize the treatment (Fischbach et al. 2005). A complete dialysis dose should consist of a urea dialysis dose and a determined convective volume. Intensified and more frequent dialysis regimens should not be considered exclusively as rescue therapy. Interestingly, a recent single-center study demonstrated that frequent on-line HDF provides an optimal dialysis prescription, both in terms of blood pressure control (and therefore avoidance of left ventricular hypertrophy), and catch-up growth, that is, no malnutrition or cachexia and less resistance to growth hormone. Nevertheless, this one-center experience would benefit from a prospective randomized study.